Introduction to computer science with C++ - Lambert, Kenneth Alfred, 1951-; Nance, Douglas W.; Naps, Thomas L. (Pacific Grove, CA : Brooks/Cole, 2000)
This book is about: Computer science, computer architecture, and computer languages; Problem-solving fundamentals; More problem-solving fundamentals; Subprograms; ...
Keywords: C++.; Computer science; Computer program language; Computer science; C++ (Computer program language)